Proposal for organizational restructuring in the institutional framework governing mining management in Antioquia - David Oliveros-Sepúlveda; Marc Bascompta-Massanés; Lluis Sanmiquel-Pera; Giovanni Franco-Sepúlveda (Social Sciences and Humanities Open)
The mining sector in the department of Antioquia, Colombia, is managed by two types of entities that operate separately and independently: the Departmental Ministry of Mines and the Regional Autonomous Corporations (CAR). These institutions have organizational structures based on a professional bureaucratic model and agency-based frameworks, which results in a series of limitations in proper intervention and a comprehensive understanding of the industry. Based on the available literature, a thorough analysis of data, and the development of a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis of the current organizational structure, this study examines the experience of Catalonia, Spain, where a different organizational model with more modern management processes has been implemented. In this context, we propose an organizational reform to the existing structural model in the department, aiming to improve the activities of monitoring, control, and approval of mining titles, thus seeking better environmental and economic outcomes for the country and its regions. The proposed model presents a series of benefits and challenges that must be evaluated by both the central and departmental governments. This analysis is crucial for the formulation of public policies aimed at achieving a more sustainable and participatory mining sector.